Increased Safety for the Community when Using Ferries Transportation - Sa’atun, Siti; Panggabean, Yunita (KnE Social Sciences, 2021)
Ferries transportation is transportation that can connect one area to area two, or we can call it a bridge. As a bridge whose function is to connect, of course many people will take advantage of ferries transportation. Due to the large number of people who use ferries transportation optimally, the needs of the users must take precedence. Virtue for Society is a factor of Safety and Comfort. Activities in optimizing community safety are carried out by means of research looking for data from one or more existing data, there is an analysis of the data obtained. In an effort to find solutions to existing problems, research is carried out that is looking for related data and comparing it with cases that have occurred. Keywords: Safety, Ferries, Transportation